From plastic waste to bioprocesses: Using ethylene glycol from polyethylene terephthalate biodegradation to fuel Escherichia coli metabolism and produce value-added compounds - Alexandra Balola; Sofia Ferreira; Isabel Rocha (Metabolic Engineering Communications)
Polyethylene Terephthalate (PET) is a petroleum-based plastic polymer that, by design, can last decades, if not hundreds of years, when released into the environment through plastic waste leakage. In the pursuit of sustainable solutions to plastic waste recycling and repurposing, the enzymatic depolymerization of PET has emerged as a promising green alternative. However, the metabolic potential of the resulting PET breakdown molecules, such as the two-carbon (C2) molecule ethylene glycol (EG), remains largely untapped. Here, we review and discuss the current state of research regarding existing natural and synthetic microbial pathways that enable the assimilation of EG as a carbon and energy source for Escherichia coli. Leveraging the metabolic versatility of E. coli, we explore the viability of this widely used industrial strain in harnessing EG as feedstock for the synthesis of target value-added compounds via metabolic and protein engineering strategies. Consequently, we assess the potential of EG as a versatile alternative to conventional carbon sources like glucose, facilitating the closure of the loop between the highly available PET waste and the production of valuable biochemicals. This review explores the interplay between PET biodegradation and EG metabolism, as well as the key challenges and opportunities, while offering perspectives and suggestions for propelling advancements in microbial EG assimilation for circular economy applications.